1982
DOI: 10.1111/j.1365-2990.1982.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Lymphocytic Populations in Human Trigeminal Ganglia: Implications for Ageing and for Latent Virus

Abstract: The number of neurones and of lymphocytes was determined morphometrically in serial sections of trigeminal ganglia harvested at autopsy from 64 human subjects dying at ages 2 months to 81 years. The nerve cell population varied from 20 159 to 156 702 with a mean of 80 638 /ganglion and was unaffected by increasing age. The degree of lymphocytic infiltration, which was prominent and ubiquitous, also did not correlate with the subjects' age. There was no significant correlation between neuronal and lymphocyte co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Lungu et al (22,23) estimated that 5 to 30% of both neurons and satellite cells are positive for VZV DNA or VZV proteins, an estimate that is far higher than that permitted by these data. Kennedy et al (17), however, estimated by in situ PCR that 2% of neurons (ϳ1,600 cells according to the estimate of Ball et al [2]) and 0.1% of satellite cells (ϳ8,000 cells according to our estimate) are VZV DNA positive. If the estimate of Kennedy et al is correct, the 7.7 ϫ 10 4 VZV genomes could persist in this number of cells at a density of eight copies/cell, not dissimilar from that for HSV-1.…”
contrasting
confidence: 51%
“…Lungu et al (22,23) estimated that 5 to 30% of both neurons and satellite cells are positive for VZV DNA or VZV proteins, an estimate that is far higher than that permitted by these data. Kennedy et al (17), however, estimated by in situ PCR that 2% of neurons (ϳ1,600 cells according to the estimate of Ball et al [2]) and 0.1% of satellite cells (ϳ8,000 cells according to our estimate) are VZV DNA positive. If the estimate of Kennedy et al is correct, the 7.7 ϫ 10 4 VZV genomes could persist in this number of cells at a density of eight copies/cell, not dissimilar from that for HSV-1.…”
contrasting
confidence: 51%
“…The source of the light chains in their patients or the present case remains a matter of speculation but the selective involvement of the trigeminal ganglion may be related to the number of lymphocytes that are present within it. In contrast to the paucity of lymphocytes in normal dorsal root and autonomic ganglia [6], Ball et al [1] observed relatively large numbers of lymphocytes in an unselected series of trigeminal ganglia obtained at autopsy. They speculated that this may have been related to previous herpes simplex virus infection.…”
Section: Discussionmentioning
confidence: 93%
“…12 Should such immunoprotection fail later in life, perhaps the reactivating HSV-1 can then creep inexorably along those trigeminal branches, entering the lower brainstem, and thence into entorhinal and eventually many more distant cortical nerve cells.…”
Section: Neuropathological Evidencementioning
confidence: 99%